2021
DOI: 10.1111/inr.12679
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting frontline Korean nurses’ mental health during the COVID‐19 pandemic

Abstract: Aim To identify the factors affecting fear, anxiety and depressive symptoms among frontline nurses working with COVID‐19 patients or are in charge of COVID‐19 screening in Korea. Background Nurses are at a higher risk of COVID‐19 infection because they are in closer, longer‐duration contact with patients. These situations can negatively affect the mental health of nurses. Methods This study analysed data from COVID‐19 module in the Korean Nurses’ Health Study. Data from 906 participants were analysed. To ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 41 publications
0
34
0
8
Order By: Relevance
“…As shown in accumulating studies, unmanageable psychological stress and emotional exhaustion was prevalent in nurses during the pandemic ( Galanis et al., 2021 ; Lai et al., 2020 ; Stelnicki et al., 2020 ). Risk factors associated with poorer mental health and functioning among nurses were extensive and complicated, including female, younger age, lack of social support, longer working time, increased workload, inadequate personal protective equipment, fear of infection, perceived hospital safety climate, isolation from family and others ( Cho et al., 2021 ; Galanis et al., 2021 ; Stelnicki et al., 2020 ). Previous studies have indicated that working in an area dedicated to COVID-19 patients was associated with worse acute mental health outcome ( Ferry et al., 2021 ; Lai et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in accumulating studies, unmanageable psychological stress and emotional exhaustion was prevalent in nurses during the pandemic ( Galanis et al., 2021 ; Lai et al., 2020 ; Stelnicki et al., 2020 ). Risk factors associated with poorer mental health and functioning among nurses were extensive and complicated, including female, younger age, lack of social support, longer working time, increased workload, inadequate personal protective equipment, fear of infection, perceived hospital safety climate, isolation from family and others ( Cho et al., 2021 ; Galanis et al., 2021 ; Stelnicki et al., 2020 ). Previous studies have indicated that working in an area dedicated to COVID-19 patients was associated with worse acute mental health outcome ( Ferry et al., 2021 ; Lai et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, understaffing characterizing the healthcare and long-term care sector before and during the pandemic entailed elevated patient-professional ratios and long-working hours, increasing exposure to emotional demands, and causing higher emotional exhaustion ( Cramer and Hunter, 2019 ). Furthermore, given the lack of protective measures and the long hours of exposure, nurses, nursing assistants and geriatric assistants were concerned about becoming infected and transmitting COVID-19 to the family ( Cho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that nurses are at higher risk of contracting COVID-19 because they are in closer and longer contact with patients. This situation can have a negative impact on the mental health of nurses (Cho et al, 2021). Nurses are on the guard Nurses become very vulnerable to many work-related hazards and experience a great amount of emotional stress in relation to jobdesk work (Aliet al, 2021).…”
Section: Introductionmentioning
confidence: 99%